Biopolymers Online 2001
DOI: 10.1002/3527600035.bpol1005
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Lignin

Abstract: Introduction Historical Outline Bacteria and Microfungi Actinomycetes Other Bacteria Soft‐Rot Fungi and Other Microfungi Brown‐Rot Basidiomycetes White‐Rot Basidiomycetes Mineralization of 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 282 publications
4
131
0
12
Order By: Relevance
“…Berg (2014) reported that groups of microorganisms that cause white rot and brown rot can be related to N and Mn contents. Fungi that cause white rot have the ability to completely degrade lignin and lignified tissues, whereas microorganisms that cause brown-colored rot are limited to breaking the side chain of the aromatic nucleus of the lignin molecule (Hatakka, 2001). Our results, observed in the field, showed higher amounts of white rot in the combinations of gliricidia, whereas brown rot was observed in greater amounts in the combinations with leucena.…”
Section: Discussionsupporting
confidence: 37%
See 1 more Smart Citation
“…Berg (2014) reported that groups of microorganisms that cause white rot and brown rot can be related to N and Mn contents. Fungi that cause white rot have the ability to completely degrade lignin and lignified tissues, whereas microorganisms that cause brown-colored rot are limited to breaking the side chain of the aromatic nucleus of the lignin molecule (Hatakka, 2001). Our results, observed in the field, showed higher amounts of white rot in the combinations of gliricidia, whereas brown rot was observed in greater amounts in the combinations with leucena.…”
Section: Discussionsupporting
confidence: 37%
“…Berg (2014) reports that the litter in which white rot fungi dominates, degradation would remain unimpeded, especially at low N concentrations, which was also observed in our study, where combinations with gliricidia showed faster decomposition than combinations with leucaena. According to Hatakka (2001) almost all fungi of white rot have Mn peroxide (MnP) and their activity would be related to the availability of Mn. In contrast, no brown rot fungus was found with MnP.…”
Section: Discussionmentioning
confidence: 99%
“…Brown rot fungi are well characterised as rapid cellulose and hemicellulose degraders, and they access plant polysaccharides by potentially modifying or degrading lignin (Hatakka 2005). These fungi are the major invaders of forest biomass and wood-based constructions.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2008) noted that the use of solid state fermentation of the enzymatic activities produced MnP (9.67 UI.L -1 ) as compared to the liquid fermentation (0.044 UI.L -1 ) especially with agroindustrial residues, which allows the concentrated product (Liu et al, 2011). Hatakka (2001) reported that the degradation of lignin by L. edodes occurred during the secondary metabolism and nitrogen reached high levels of lignocellulosic degradation.…”
Section: Treatments Daysmentioning
confidence: 99%